Proton exchange membrane and preparation method and application thereof
By using materials such as epoxy cage polysilsesquioxane and polybenzimidazole, combined with two-stage heat treatment processes, the prepared proton exchange membrane solves the problem of the lack of obvious proton conductivity at high temperatures in traditional high-temperature proton exchange membranes, and significantly improves the proton conductivity and mechanical properties.
Patent Information
- Application Number
- CN202510103081.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The proton conductivity of traditional high-temperature proton exchange membranes is not obvious at high temperatures, which affects the electrochemical performance of fuel cells.
A proton exchange membrane was prepared by using epoxy cage-shaped polysilsesquioxane as a crosslinking agent, combined with polybenzimidazole and two-stage heat treatment process. This method adsorbs phosphoric acid through cage-like structures, reduces phosphoric acid loss, and improves mechanical properties through cross-linking.
The proton conductivity of the proton exchange membrane in a wide temperature domain is significantly improved, mechanical properties are enhanced, phosphoric acid loss is reduced, and electrochemical performance of fuel cells is improved.
Smart Images

Figure CN119890376A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of fuel cells, and in particular relates to a proton exchange membrane and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cell (PEMFC) is a highly efficient energy conversion device that can directly convert the chemical energy of fuel into electrical energy without combustion. According to the temperature, PEMFC can be divided into high-temperature proton exchange membrane fuel cell (HT-PEMFC) and low-temperature proton exchange membrane fuel cell (LT-PEMFC).
[0003] As the core component of PEMFC, proton exchange membrane plays a decisive role in the operating temperature and electrochemical performance of fuel cells. The main operating temperature of traditional high-temperature proton exchange membrane is 100~200℃. Due to the plasticizing effect of phosphoric acid and the loss of phosphoric acid at high temperature, when the proton exchange membrane works at 240℃, its proton conductivity is not significantly improved with molecular dynamics, which in turn affects the electrochemical performance of the fuel cell. Summary of the invention
[0004] In view of the defects and shortcomings of the prior art, in the first aspect, the present invention provides a method for preparing a proton exchange membrane; in the second aspect, the present invention provides a proton exchange membrane; in the third aspect, the present invention provides a battery.
[0005] In a first aspect, the present invention provides a method for preparing a proton exchange membrane, comprising the following steps: Step 1, mixing epoxy caged polysilsesquioxane and an organic solvent to obtain solution A; mixing polybenzimidazole, anhydrous lithium chloride and an organic solvent and heating and stirring under an oxygen-free atmosphere to obtain solution B; Step 2, mixing solution A and solution B and heating and stirring in an oxygen-free atmosphere to obtain a casting solution; Step 3, applying the casting solution onto the substrate by scraping, and vacuum drying to obtain an intermediate product A; Step 4, immersing the intermediate product A in a first phosphoric acid solution, and then heat treating it at 60-80° C. for a certain period of time in an air atmosphere to obtain an intermediate product B; Step 5: Apply the second phosphoric acid solution to both sides of the intermediate product B respectively, and then heat treat it at 150-200° C. for a certain time in an inert atmosphere to obtain the proton exchange membrane.
[0006] Preferably, the structural formula of the epoxy cage-like polysilsesquioxane is as follows: .
[0007] Preferably, the polybenzimidazole includes any one or more of N-PBI (poly 2,2-(p-naphthylene)-5,5′-dibenzimidazole), m-PBI (poly 2,2-(m-phenylene)-5,5′-dibenzimidazole), p-PBI (poly 2,2-(p-phenylene)-5,5′-dibenzimidazole), OPBI (ether-bonded polybenzimidazole), AmPBI (aminopolybenzimidazole), BPPBI (pyridylpolybenzimidazole), and PBIOH (hydroxypolybenzimidazole).
[0008] Preferably, the organic solvents in the solution A and the solution B are one or more of N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide and tetrahydrofuran.
[0009] Preferably, the mass ratio of the epoxy cage-like polysilsesquioxane to the organic solvent in the solution A is 1:20-100.
[0010] Preferably, the mass ratio of polybenzimidazole, anhydrous lithium chloride and organic solvent in the solution B is 1:0.05-0.25:20-25.
[0011] Preferably, in step 2, the mass ratio of epoxy cage-like polysilsesquioxane to polybenzimidazole in the solution A and the solution B is 1:4-20.
[0012] Preferably, in step 1, epoxy caged polysilsesquioxane and an organic solvent are mixed and stirred at room temperature for 3 to 5 hours to obtain solution A; polybenzimidazole, anhydrous lithium chloride and an organic solvent are mixed and stirred at 70 to 80° C. for 3 to 5 hours to obtain solution B.
[0013] Preferably, in step 2, the heating temperature is 50-80° C. and the heating time is 0.5-1 h.
[0014] Preferably, in step 3, the coating thickness is 200-1200 μm.
[0015] Preferably, in step 3, the drying temperature is 120-150° C. and the drying time is 8-12 hours.
[0016] Preferably, between step 3 and step 4, the process further comprises: allowing the intermediate product A to stand in the air for 24-36 hours.
[0017] Preferably, in step 4, the heat treatment time is 36 to 72 hours.
[0018] In step 5, the mass ratio of the second phosphoric acid solution to the intermediate product B used for each brushing is 1:0.25-0.35.
[0019] Preferably, in step 5, the heat treatment time is 2 to 12 hours.
[0020] Preferably, in step 4 and step 5, the mass fractions of the first phosphoric acid solution and the second phosphoric acid solution are both 75% to 85%.
[0021] Preferably, in step 4, the intermediate product A is completely immersed in the first phosphoric acid solution.
[0022] Preferably, in step 5, the inert gas providing the inert atmosphere is nitrogen or argon.
[0023] In a second aspect, the present invention provides a proton exchange membrane prepared by the above preparation method.
[0024] In a third aspect, the present invention provides a battery comprising the above-mentioned proton exchange membrane.
[0025] Compared with the prior art, the present invention has the following obvious beneficial effects: (1) When preparing the proton exchange membrane in the present invention, the cross-linking agent is selected from epoxy cage-like polysilsesquioxane. On the one hand, the cage-like structure has a larger free volume, which can adsorb more phosphoric acid and reduce the possibility of subsequent phosphoric acid loss. On the other hand, the epoxy cage-like polysilsesquioxane has good high temperature resistance and good compatibility with polybenzimidazole. The two can be fully cross-linked during the heat treatment process, further improving the mechanical properties of the proton exchange membrane. On the third hand, the combination of epoxy cage-like polysilsesquioxane and the two-stage heat treatment process can further reduce the possibility of phosphoric acid loss and improve the proton conductivity of the proton exchange membrane in a wide temperature range.
[0026] (2) The preparation process provided by the present invention is simple and controllable, which is conducive to large-scale production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The Fourier transform infrared spectra of the intermediate product A, epoxy caged polysilsesquioxane (G-POSS) and polybenzimidazole (PBI) obtained in step 3 of Example 1; Figure 2 The proton conductivity curves of the proton exchange membranes prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 4; Figure 3 The mechanical property test performance diagram of the proton exchange membranes prepared in Example 1 and Comparative Examples 1, 2, and 4. DETAILED DESCRIPTION
[0028] The present invention provides the following specific technical solutions.
[0029] In a first aspect, the present invention provides a method for preparing a proton exchange membrane, comprising the following steps: Step 1, mixing epoxy caged polysilsesquioxane and an organic solvent to obtain solution A; mixing polybenzimidazole, anhydrous lithium chloride and an organic solvent and heating and stirring under an oxygen-free atmosphere to obtain solution B; Step 2, mixing solution A and solution B and heating and stirring in an oxygen-free atmosphere to obtain a casting solution; Step 3, applying the casting solution onto the substrate by scraping, and vacuum drying to obtain an intermediate product A; Step 4, immersing the intermediate product A in a first phosphoric acid solution, and then heat treating it at 60-80° C. for a certain period of time in an air atmosphere to obtain an intermediate product B; Step 5: Apply the second phosphoric acid solution to both sides of the intermediate product B respectively, and then heat treat it at 150-200° C. for a certain time in an inert atmosphere to obtain the proton exchange membrane.
[0030] The inventors have found through research that, firstly, the proton exchange membrane prepared by using epoxy caged polysilsesquioxane as a crosslinking agent has a large free volume, and there is a large amount of space not occupied by molecules in the proton exchange membrane, which can make the proton exchange membrane absorb more phosphoric acid when soaked in phosphoric acid in the first stage, thereby reducing the influence of phosphoric acid loss on battery performance during the operation of the proton exchange membrane; secondly, the oxygen caged polysilsesquioxane has good high temperature resistance, and the epoxy caged polysilsesquioxane is a cage-type polysilsesquioxane molecule with a three-dimensional nano-scale organic / inorganic hybrid structure, which has good compatibility with polybenzimidazole (PBI), and the two are fully crosslinked during the heat treatment process, thereby further improving the mechanical properties of the proton exchange membrane; thirdly, the two-stage heat treatment process provided by the present invention can make the polybenzimidazole and the crosslinking agent fully crosslinked, and the mechanical properties of the proton exchange membrane are further enhanced, and the cage structure of the epoxy caged polysilsesquioxane can lock the doped phosphoric acid during the crosslinking process, thereby reducing the possibility of phosphoric acid loss, and further improving the proton conductivity of the proton exchange membrane in a wide temperature range.
[0031] The inventors further discovered that applying the second phosphoric acid solution to both sides of the intermediate product B can prevent the intermediate product B from swelling at 150-200°C, and can allow the proton exchange membrane to adsorb a small amount of phosphoric acid again, thereby improving the proton conduction performance at high temperatures.
[0032] Preferably, the structural formula of the epoxy cage-like polysilsesquioxane is as follows: .
[0033] The reaction process of the epoxy cage-like polysilsesquioxane and the polybenzimidazole is as follows: .
[0034] Preferably, the polybenzimidazole includes any one or more of N-PBI (poly 2,2-(p-naphthylene)-5,5′-dibenzimidazole), m-PBI (poly 2,2-(m-phenylene)-5,5′-dibenzimidazole), p-PBI (poly 2,2-(p-phenylene)-5,5′-dibenzimidazole), OPBI (ether-bonded polybenzimidazole), AmPBI (aminopolybenzimidazole), BPPBI (pyridylpolybenzimidazole), and PBIOH (hydroxypolybenzimidazole).
[0035] Preferably, the organic solvents in the solution A and the solution B are one or more of N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide and tetrahydrofuran.
[0036] Preferably, the mass ratio of the epoxy cage-like polysilsesquioxane to the organic solvent in the solution A is 1:20-100.
[0037] Preferably, the mass ratio of polybenzimidazole, anhydrous lithium chloride and organic solvent in the solution B is 1:0.05-0.25:20-25.
[0038] The above ratio is the preferred range given by the inventor after many studies. The proton exchange membrane prepared within this range has good ductility and uniform texture. In practical applications, the above ratio can be adjusted according to the ambient temperature and humidity. In a specific embodiment of the present invention, the mass ratio of epoxy cage-like polysilsesquioxane and organic solvent in solution A can be 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90 and 1:100; the mass ratio of polybenzimidazole, anhydrous lithium chloride and organic solvent in solution B can be 1:0.05:20, 1:0.1:21, 1:0.15:22, 1:0.2:23, 1:0.25:25.
[0039] Preferably, in step 2, the mass ratio of epoxy cage-like polysilsesquioxane to polybenzimidazole in the solution A and the solution B is 1:4-20.
[0040] The inventors have found through research that polybenzimidazole itself has excellent thermal stability, chemical stability and flame retardancy. The proton exchange membrane prepared by the reaction of excess polybenzimidazole and epoxy caged polysilsesquioxane not only inherits the excellent performance of polybenzimidazole itself, but also has a more uniform and dense structure, which is conducive to improving the proton conductivity of the proton exchange membrane and preventing gas permeation. In actual application, the mass ratio of epoxy caged polysilsesquioxane to polybenzimidazole in solution C can be 1:4, 1:8, 1:12, 1:16, 1:20.
[0041] Preferably, in step 1, epoxy caged polysilsesquioxane and an organic solvent are mixed and stirred at room temperature for 3 to 5 hours to obtain solution A; polybenzimidazole, anhydrous lithium chloride and an organic solvent are mixed and stirred at 70 to 80° C. for 3 to 5 hours to obtain solution B.
[0042] In actual operation, the time for stirring the epoxy cage-like polysilsesquioxane and the organic solvent can be adjusted according to the actual operation conditions, and the stirring is performed until the epoxy cage-like polysilsesquioxane is dissolved in the organic solvent.
[0043] Preferably, in step 2, the heating temperature is 50-80° C. and the heating time is 0.5-1 h.
[0044] Preferably, in step 3, the coating thickness is 200-1200 μm.
[0045] Preferably, in step 3, the drying temperature is 120-150° C. and the drying time is 8-12 hours.
[0046] Preferably, between step 3 and step 4, the process further comprises: allowing the intermediate product A to stand in the air for 24-36 hours.
[0047] The inventors have found through research that placing the intermediate product in the air for a certain period of time can allow the anhydrous lithium chloride in product A to absorb moisture in the air, which is beneficial to improving the efficiency of subsequent proton exchange membrane adsorption of phosphoric acid.
[0048] Preferably, in step 4, the soaking time is 36 to 72 hours.
[0049] In step 5, the mass ratio of the second phosphoric acid solution to the intermediate product B used for each brushing is 1:0.25-0.35.
[0050] Preferably, in step 5, the heat treatment time is 2 to 12 hours.
[0051] Preferably, in step 4 and step 5, the mass fractions of the first phosphoric acid solution and the second phosphoric acid solution are both 75% to 85%.
[0052] Preferably, in step 4, the intermediate product A is completely immersed in the first phosphoric acid solution.
[0053] The inventors have found through research that completely immersing the intermediate product A in the first phosphoric acid solution in step 4 is beneficial for the intermediate product A to fully absorb phosphoric acid and improve the doping efficiency of phosphoric acid.
[0054] Preferably, in step 5, the inert gas providing the inert atmosphere is nitrogen or argon.
[0055] In a second aspect, the present invention provides a proton exchange membrane prepared by the above preparation method.
[0056] In a third aspect, the present invention provides a battery comprising the above-mentioned proton exchange membrane.
[0057] In order to make the technical problems, technical solutions and technical advantages to be solved by the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.
[0058] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0059] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0060] Embodiment 1: A method for preparing a proton exchange membrane comprises the following steps: Step 1, add 0.1 g of epoxy caged polysilsesquioxane to 2 mL of dimethyl sulfoxide solution, stir at room temperature for 5 h to obtain solution A; add 0.4 g of polybenzimidazole and 0.1 g of anhydrous lithium chloride to 8 mL of dimethyl sulfoxide, heat treat in an oil bath at 70° C. in an oxygen-free atmosphere and stir for 5 h to obtain solution B.
[0061] Step 2: After mixing solution A and solution B, heat-treat to 70° C. in an oxygen-free atmosphere and stir until the mixture is uniform, thereby obtaining a casting solution.
[0062] Step 3, scrape the casting solution onto a flat glass plate with a coating thickness of 700 μm, then transfer the glass plate to a vacuum drying oven, heat it from 80° C. to 150° C. and keep it warm for 8 hours to obtain intermediate product A.
[0063] Step 4, place the intermediate product A in air for 48 hours.
[0064] Step 5, completely immersing the intermediate product A treated in step 4 in a phosphoric acid solution with a mass fraction of 85% and heat-treating it at 70° C. for 48 hours, and the obtained film is the intermediate product B; Step 6, placing the intermediate product B in a high-temperature container, then dropping a phosphoric acid solution with a mass fraction of 85% on one side of the intermediate product B, brushing it evenly and then turning the intermediate product B over, and again dropping a phosphoric acid solution with a mass fraction of 85% on the other side of the intermediate product B, brushing it evenly, the mass ratio of the phosphoric acid solution dropped on the intermediate product B each time to the intermediate product B is 1:0.3, and then placing the intermediate product B brushed with the phosphoric acid solution in an argon atmosphere at 180°C for heat treatment for 4 hours, and the obtained membrane is the proton exchange membrane.
[0065] Figure 1 The Fourier transform infrared spectra of the intermediate product A, epoxy caged polysilsesquioxane (G-POSS) and polybenzimidazole (PBI) obtained in step 3 of Example 1 are shown in FIG. Figure 1 It can be observed that the Fourier infrared curve of intermediate product A is at 910 cm -1 The peak of epoxy group appears at , indicating that the epoxy group reacts with the imidazole group and successfully forms a proton exchange membrane.
[0066] Comparative Example 1: A method for preparing a proton exchange membrane comprises the following steps: Step 1, add 0.1 g of epoxy caged polysilsesquioxane to 2 mL of dimethyl sulfoxide, and stir at room temperature for 5 h to obtain solution A; add 0.4 g of polybenzimidazole and 0.1 g of anhydrous lithium chloride to 8 mL of dimethyl sulfoxide, heat treat in an oil bath at 70° C. in an oxygen-free atmosphere and stir for 5 h to obtain solution B.
[0067] Step 2: After mixing solution A and solution B, heat-treat to 70° C. in an oxygen-free atmosphere and stir until the mixture is uniform, thereby obtaining a casting solution.
[0068] Step 3, scrape the casting solution onto a flat glass plate, then transfer the glass plate into a vacuum drying oven, heat it from 80° C. to 150° C. and keep it warm for 8 hours to obtain an intermediate product A.
[0069] Step 4, place the intermediate product A in air for 48 hours.
[0070] Step 5, completely immersing the intermediate product A treated in step 4 in a phosphoric acid solution with a mass fraction of 85% for 48 hours, and the obtained membrane is a proton exchange membrane.
[0071] Comparative Example 2: A method for preparing a proton exchange membrane comprises the following steps: Step 1, add 0.1 g of epoxy caged polysilsesquioxane to 2 mL of dimethyl sulfoxide, and stir at room temperature for 5 h to obtain solution A; add 0.4 g of polybenzimidazole and 0.1 g of anhydrous lithium chloride to 8 mL of dimethyl sulfoxide, heat treat in an oil bath at 70° C. in an oxygen-free atmosphere and stir for 5 h to obtain solution B.
[0072] Step 2: After mixing solution A and solution B, heat-treat to 70° C. in an oxygen-free atmosphere and stir until the mixture is uniform, thereby obtaining a casting solution.
[0073] Step 3, scrape the casting solution onto a flat glass plate, then transfer the glass plate into a vacuum drying oven, heat it from 80° C. to 150° C. and keep it warm for 8 hours to obtain an intermediate product A.
[0074] Step 4, place the intermediate product A in air for 48 hours.
[0075] Step 5, completely immersing the intermediate product A treated in step 4 in a phosphoric acid solution with a mass fraction of 85% and heat-treating it at 70° C. for 48 hours, and the obtained film is the intermediate product B; Step 6, placing the intermediate product B in a high-temperature container, then dropping a phosphoric acid solution with a mass fraction of 85% on one side of the intermediate product B, brushing it evenly and then turning the intermediate product B over, and again dropping a phosphoric acid solution with a mass fraction of 85% on the other side of the intermediate product B, brushing it evenly, the mass ratio of the phosphoric acid solution dropped on the intermediate product B each time to the intermediate product B is 1:0.3, and then placing the intermediate product B brushed with the phosphoric acid solution in an argon atmosphere at 70°C for heat treatment for 4 hours, and the obtained membrane is the proton exchange membrane.
[0076] Comparative Example 3: A method for preparing a proton exchange membrane comprises the following steps: Step 1, add 0.1 g of epoxy caged polysilsesquioxane to 2 mL of dimethyl sulfoxide, and stir at room temperature for 5 h to obtain solution A; add 0.4 g of polybenzimidazole and 0.1 g of anhydrous lithium chloride to 8 mL of dimethyl sulfoxide, heat treat in an oil bath at 70° C. in an oxygen-free atmosphere and stir for 5 h to obtain solution B.
[0077] Step 2: After mixing solution A and solution B, heat-treat to 70° C. in an oxygen-free atmosphere and stir until the mixture is uniform, thereby obtaining a casting solution.
[0078] Step 3, scrape the casting solution onto a flat glass plate, then transfer the glass plate into a vacuum drying oven, heat it from 80° C. to 150° C. and keep it warm for 8 hours to obtain an intermediate product A.
[0079] Step 4, place the intermediate product A in air for 48 hours.
[0080] Step 5, the intermediate product A treated in step 4 was completely immersed in a phosphoric acid solution with a mass fraction of 85% and heat treated at 180°C. After 10 hours, it was observed that the intermediate product A swelled and dissolved in the phosphoric acid solution, and subsequent experiments and tests could not be carried out.
[0081] Comparative Example 4: A method for preparing a proton exchange membrane comprises the following steps: Step 1, add 0.1 g of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane (KH560) to 2 mL of dimethyl sulfoxide, and stir at room temperature for 5 hours to obtain solution A; add 0.4 g of polybenzimidazole and 0.1 g of anhydrous lithium chloride to 8 mL of dimethyl sulfoxide, heat treat in an oil bath at 70°C in an oxygen-free atmosphere and stir for 5 hours to obtain solution B.
[0082] Step 2: After mixing solution A and solution B, heat-treat to 70° C. in an oxygen-free atmosphere and stir until the mixture is uniform, thereby obtaining a casting solution.
[0083] Step 3, scrape the casting solution onto a flat glass plate, then transfer the glass plate into a vacuum drying oven, heat it from 80° C. to 150° C. and keep it warm for 8 hours to obtain an intermediate product A.
[0084] Step 4, place the intermediate product A in air for 48 hours.
[0085] Step 5, completely immersing the intermediate product A treated in step 4 in a phosphoric acid solution with a mass fraction of 85% and heat-treating it at 70° C. for 48 hours, and the obtained film is the intermediate product B; Step 6, placing the intermediate product B in a high-temperature container, then dropping a phosphoric acid solution with a mass fraction of 85% on one side of the intermediate product B, brushing it evenly and then turning the intermediate product B over, and again dropping a phosphoric acid solution with a mass fraction of 85% on the other side of the intermediate product B, brushing it evenly, the mass ratio of the phosphoric acid solution dropped on the intermediate product B each time to the intermediate product B is 1:0.3, and then placing the intermediate product B brushed with the phosphoric acid solution in an argon atmosphere at 180°C for heat treatment for 4 hours, and the obtained membrane is the proton exchange membrane.
[0086] Embodiment 2: A method for preparing a proton exchange membrane comprises the following steps: Step 1, add 0.1 g of epoxy cage polysilsesquioxane to 2 mL of N,N-dimethylformamide, and stir at room temperature for 5 hours to obtain solution A; add 1 g of polybenzimidazole and 0.05 g of anhydrous lithium chloride to 23 mL of N,N-dimethylformamide, heat treat in an oil bath at 80°C in an oxygen-free atmosphere and stir for 3 hours to obtain solution B.
[0087] Step 2: Mix solution A and solution B, heat-treat at 80° C. in an oxygen-free atmosphere, and stir until the mixture is uniform to obtain a casting solution.
[0088] Step 3, scrape the casting solution onto a flat glass plate, then transfer the glass plate into a vacuum drying oven, heat it from 80° C. to 150° C. and keep it warm for 12 hours to obtain an intermediate product A.
[0089] Step 4, place the intermediate product A in air for 48 hours.
[0090] Step 5, immersing the intermediate product A treated in step 4 in a 75% by mass phosphoric acid solution and heat treating it at 60° C. for 72 hours, and the obtained film is the intermediate product B; Step 6, placing the intermediate product B in a high-temperature container, then dropping a 75% by mass phosphoric acid solution on one side of the intermediate product B, brushing it evenly and then turning the intermediate product B over, and again dropping a 75% by mass phosphoric acid solution on the other side of the intermediate product B, brushing it evenly, the mass ratio of the phosphoric acid solution dropped on the intermediate product B each time to the intermediate product B is 0.35, and then placing the intermediate product B brushed with the phosphoric acid solution in an argon atmosphere for heat treatment at 200°C for 12 hours, and the obtained membrane is the proton exchange membrane.
[0091] Embodiment 3: A method for preparing a proton exchange membrane comprises the following steps: Step 1, add 0.02 g of epoxy caged polysilsesquioxane to 2 mL of tetrahydrofuran, and stir at room temperature for 5 h to obtain solution A; add 0.4 g of polybenzimidazole and 0.07 g of anhydrous lithium chloride to 10 mL of tetrahydrofuran, heat treat in an oil bath at 70° C. in an oxygen-free atmosphere and stir for 3 h to obtain solution B.
[0092] Step 2: After mixing solution A and solution B, heat-treat to 70° C. in an oxygen-free atmosphere and stir until the mixture is uniform, thereby obtaining a casting solution.
[0093] Step 3, scrape the casting solution onto a flat glass plate, then transfer the glass plate into a vacuum drying oven, raise the temperature from 80° C. to 130° C. and keep it warm for 8 hours to obtain an intermediate product A.
[0094] Step 4, place the intermediate product A in air for 48 hours.
[0095] Step 5, immersing the intermediate product A treated in step 4 in a phosphoric acid solution with a mass fraction of 80% and heat-treating it at 80° C. for 72 hours, and the obtained film is the intermediate product B; Step 6, placing the intermediate product B in a high-temperature container, then dropping a phosphoric acid solution with a mass fraction of 80% on one side of the intermediate product B, brushing it evenly and then turning the intermediate product B over, and again dropping a phosphoric acid solution with a mass fraction of 80% on the other side of the intermediate product B, brushing it evenly, the mass ratio of the phosphoric acid solution dropped on the intermediate product B each time to the intermediate product B is 1:0.25, and then placing the intermediate product B brushed with the phosphoric acid solution in an argon atmosphere at 150°C for heat treatment for 12 hours, and the obtained membrane is the proton exchange membrane.
[0096] Figure 2 The proton conductivity curves of the proton exchange membranes prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 4 are shown in FIG. Figure 2It can be seen that the proton conductivity of the proton exchange membrane prepared in Example 1 is higher than the proton conductivity of the proton exchange membrane prepared in Comparative Example 1. In the range of 100-250°C, the proton conductivity of the proton exchange membrane prepared in Example 1 is significantly improved, which proves that the proton exchange membrane prepared by the two-stage heat treatment preparation process provided by the present invention has a more excellent proton conductivity. According to the trend of the proton conductivity curve, it can be reasonably inferred that the applicable temperature range of the proton exchange membrane prepared in Example 1 can also be significantly improved.
[0097] The proton conductivity of the proton exchange membrane prepared in Comparative Example 2 is lower than that of the proton exchange membrane prepared in Example 1. The inventors speculate that the reason is that the heat treatment temperature of the proton exchange membrane prepared in Comparative Example 2 is low, resulting in incomplete cross-linking reaction of the proton exchange membrane, and the doped phosphoric acid is easily lost, affecting its proton conductivity.
[0098] The proton conductivity of the proton exchange membrane prepared in Comparative Example 4 is lower than the proton conductivity of the proton exchange membrane prepared in Example 1. The inventors speculate that the reason is that when preparing the proton exchange membrane of Comparative Example 4, the cross-linking agent used does not contain a cage structure, and the binding and capture performance of phosphoric acid are reduced. Therefore, the proton conductivity of the proton exchange membrane prepared in Comparative Example 4 is the worst compared with Example 1, Comparative Example 1, and Comparative Example 2.
[0099] Depend on Figure 2 It can be clearly observed that within the range of 100-200°C, the main operating temperature of the proton exchange membrane, the proton conductivity of the proton exchange membrane prepared in Example 1 is much higher than the proton conductivity of the proton exchange membranes prepared in Comparative Examples 1, 2 and 4, and the proton conductivity increases by several times, further illustrating that the proton exchange membrane prepared by the preparation process provided by the present invention has more excellent electrochemical properties.
[0100] Figure 3 The mechanical properties test curves of the proton exchange membranes prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 4 are shown in FIG. Figure 3 It can be seen intuitively that the mechanical properties of the proton exchange membrane prepared in Example 1 are the most excellent, and its elongation at break and tensile strength are far superior to those of the proton exchange membranes prepared in Comparative Examples 1, 2 and 4.
[0101] The inventors speculate that the reasons may be: the proton exchange membrane prepared in Comparative Example 1 was not subjected to two-stage heat treatment, and the cross-linking reaction was incomplete, resulting in poor mechanical properties; although the proton exchange membrane prepared in Comparative Example 2 was subjected to two-stage heat treatment, its tensile strength was increased, but the low heat treatment temperature resulted in a decrease in its elongation at break; the cross-linking agent selected in Comparative Example 4 did not contain a cage structure, and the cross-linking agent may not have been further cross-linked after heat treatment, so the mechanical properties of the proton exchange membrane prepared in Comparative Example 4 were similar to those of Comparative Example 1.
[0102] The embodiments described above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope of the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a proton exchange membrane, characterized in that: The steps include: Step 1, mixing epoxy caged polysilsesquioxane and an organic solvent to obtain solution A; mixing polybenzimidazole, anhydrous lithium chloride and an organic solvent and heating and stirring under an oxygen-free atmosphere to obtain solution B; Step 2, mixing solution A and solution B and heating and stirring in an oxygen-free atmosphere to obtain a casting solution; Step 3, applying the casting solution onto the substrate by scraping, and vacuum drying to obtain an intermediate product A; Step 4, immersing the intermediate product A in a first phosphoric acid solution, and then heat treating it at 60-80° C. for a certain period of time in an air atmosphere to obtain an intermediate product B; Step 5: Apply the second phosphoric acid solution to both sides of the intermediate product B respectively, and then heat treat it at 150-200° C. for a certain time in an inert atmosphere to obtain the proton exchange membrane.
2. The method for preparing a proton exchange membrane according to claim 1, characterized in that: The structural formula of the epoxy cage-like polysilsesquioxane is as follows: 。 3. The method for preparing a proton exchange membrane according to claim 1, characterized in that: In step 5, the mass ratio of the second phosphoric acid solution to the intermediate product B used for each brushing is 1:0.25-0.
35.
4. A method for preparing a proton exchange membrane according to claim 1 or 2, characterized in that: The polybenzimidazole includes any one or more of N-PBI, m-PBI, p-PBI, OPBI, AmPBI, BPPBI, and PBIOH.
5. The method for preparing a proton exchange membrane according to claim 1 or 3, characterized in that: The organic solvents in the solution A and the solution B are one or more of N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide, and tetrahydrofuran; the mass ratio of the epoxy caged polysilsesquioxane to the organic solvent in the solution A is 1:20-100; the mass ratio of the polybenzimidazole, anhydrous lithium chloride, and the organic solvent in the solution B is 1:0.05-0.25:20-25; and the mass fractions of the first phosphoric acid solution and the second phosphoric acid solution are both 75%-85%.
6. A method for preparing a proton exchange membrane according to claim 1 or 2, characterized in that: In step 2, the mass ratio of epoxy cage-like polysilsesquioxane to polybenzimidazole in the solution A and the solution B is 1:4-20.
7. The method for preparing a proton exchange membrane according to claim 1, characterized in that: In step 1, epoxy caged polysilsesquioxane and an organic solvent are mixed and stirred at room temperature for 3 to 5 hours to obtain solution A; polybenzimidazole, anhydrous lithium chloride and an organic solvent are mixed and stirred at 70 to 80° C. for 3 to 5 hours to obtain solution B.
8. The method for preparing a proton exchange membrane according to claim 1, characterized in that: In step 2, the heating temperature is 50-80°C and the heating time is 0.5-1h; in step 3, the drying temperature is 120-150°C and the drying time is 8-12h; in step 4, the heat treatment time is 36-72h; in step 5, the heat treatment time is 2-12h; and between step 3 and step 4, the process also includes: allowing the intermediate product A to stand in the air for 24-36h.
9. A proton exchange membrane, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. A battery, characterized in that: Comprising the proton exchange membrane according to claim 9.
Citation Information
Patent Citations
Polybenzimidazole with cross-linked structure, high-temperature proton exchange membrane and preparation method of high-temperature proton exchange membrane
CN116284778A
Polymer electrolyte composition containing aromatic hydrocarbon-based resin and cage-like silsesquioxane
JP2007112906A
Epoxy resin containing side-chain-tethered caged POSS and preparation method thereof as well as epoxy resin material containing POSS-epoxy and preparation method thereof
US20100087616A1
Cited By
In-situ reduced MnO2 doped high-temperature proton exchange composite membrane, and preparation method and application thereof
CN122659208A